Morphology evolution of poly(lactic acid) during in situ reaction with poly(butylenesuccinate) and ethylene‐methyl acrylate‐glycidyl methacrylate: The formation of a novel 3D star‐like structure. Issue 40 (9th March 2020) - Xue, Bin; He, He‐Zhi; Huang, Zhao‐Xia; Zhu, Zhiwen; Li, Jiqian; Zhan, Zhiming; Chen, Ming; Wang, Guozhen; Xiong, Chengtian
Abstract: Morphology control of polymer alloys is an attractive topic for investigators due to its ability to improve the performance of products for years. However, it is hard to control the morphology of immiscible polymer blends during melt processing. Herein, we studied the morphology evolution of poly(lactic acid) (PLA)/poly(butylene succinate) (PBS) with the inclusion of ethylene‐methyl acrylate‐glycidyl methacrylate (EGMA). Scanning electron microscopy of both cryo‐fractured and etched cryo‐fractured samples indicates that the in situ reaction among PLA, PBS, and EGMA can induce the morphology change and result in a novel 3D star‐like structure. Rheology behaviors of the samples under different angular frequencies were used to validate the formation of 3D networks in the samples. Tensile stiffness reinforcements at both room temperature and high temperature were provided through dynamic mechanical analysis. In addition, a 10‐fold improvement in impact strength is also monitored by the unnotched impact test to indicate the superior toughening effect. Furthermore, the crystalline behavior and thermal properties of the blends were also studied. It is believed that our work not only gives a deeper understanding of the reaction‐induced morphology evolution of the PLA/PBS/EGMA blends but also reveals an avenue toward morphology control by melt processing. Abstract : In this work, the reaction induced morphological variation is studied by scanning electron microscopy and rheological behavior analysis by melt compounding polylactic acid (PLA)/poly(butylene succinate) with ethylene‐methyl acrylate‐glycidyl methacrylate. The formation of a novel star‐like 3D structure is revealed by etching the amorphous PLA phase with the formation mechanism also proposed. Consequently, benefiting from such a novel structure, enhanced toughness, and high‐temperature stiffness are obtained.